COVID-19 pandemic: Direct effects on the medical education in Pakistan. (July 2022) - Siddiqi, Haziq; Tahir, Muhammad Junaid; Ullah, Irfan; Nazir, Abubakar; Douba, Zain; Asghar, Muhammad Sohaib; Yousaf, Zohaib
Highlights: To date, the medical education literature has focused on strategies for high-income countries to optimize online education. Low- and middle-income countries' students face additional challenges in providing virtual education. The main challenges LMIC students face are frequent internet and electricity outages and limited technology skills. The COVID-19 pandemic placed novel emotional and financial pressures on medical students. Here, we presented strategies for best practices in remote medical education, such as open-access medical education content.